THE IMPORTANCE OF IMAGING IN RADIATION THERAPY: A REVIEW ARTICLE - Puspasari, Aisya; Sulistyo, Rafiq (International Journal of Radiology and Imaging, 2022)
Radiotherapy is one of the modern cancer treatment modalities. Advances in medical technology have revolutionized external radiotherapy with CT scanning, allowing for the visualization and grouping of tumors and at-risk organs in a three-dimensional view. However, CT has some limitations, especially in assessing the character and delineation of tumors. PET and MRI go beyond CT in terms of functional and anatomical images. PET/CT/MRI multimodality combines the strengths of each technique without conflating their respective weaknesses, thereby strengthening the role of imaging for radiation therapy management. On account of this, it can become the primary technique in radiotherapy modalities. This review aims to describe multimodality of the PET/CT/MRI process for radiotherapy and its potential clinical applications.